2021
DOI: 10.1002/chem.202005005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electronic Properties of Directly Linked Dihydrodiazatetracene Dimers

Abstract: 5,12‐Dihydro‐5,12‐diazatetracene (DHDAT) dimers with different substitution patterns are synthesized: a symmetric one with a C−C bond between the monomer units (1) and two asymmetric ones with a C−N bond between the monomer units (2 and 3). The DHDAT units are planar in the C−C linked dimer 1 but perpendicularly oriented in the C−N linked dimers 2 and 3 (from X‐ray analysis). The electronic ground‐state interaction between the two units is large in 1 and small in 2 and 3. The emission behavior of 3 is differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These derivatives are known to be easily oxidized and have been synthesized by various groups, 27 31 leading to their use as emitters, redox-active materials, or organocatalysts. 32 37 Interestingly, while the radical cations of such derivatives have been extensively explored, 30 , 34 , 38 , 39 the aromatic dicationic diamagnetic states have been widely neglected and studied almost exclusively in solution, 39 , 40 with some notable exceptions successfully isolating N-alkyl derivatives of the parent phenazinium dication, which, however, were reported as highly reactive ( Figure 1 ). 41 , 42 More recently, an elegant work from the group of Shinokubo reported the synthesis of an anthracene-extended dihydrophenazine ( Figure 1 ), which was oxidized in solution to the radical and dicationic states, resulting in a marked electrochromism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These derivatives are known to be easily oxidized and have been synthesized by various groups, 27 31 leading to their use as emitters, redox-active materials, or organocatalysts. 32 37 Interestingly, while the radical cations of such derivatives have been extensively explored, 30 , 34 , 38 , 39 the aromatic dicationic diamagnetic states have been widely neglected and studied almost exclusively in solution, 39 , 40 with some notable exceptions successfully isolating N-alkyl derivatives of the parent phenazinium dication, which, however, were reported as highly reactive ( Figure 1 ). 41 , 42 More recently, an elegant work from the group of Shinokubo reported the synthesis of an anthracene-extended dihydrophenazine ( Figure 1 ), which was oxidized in solution to the radical and dicationic states, resulting in a marked electrochromism.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this approach could result not only in semiconducting materials presenting charge transfer states but also in the introduction of highly polar bonds that are useful for self-assembly and sensing. Moreover, the possibility of introducing the heteroatoms in a neutral state and oxidizing them in a later step can result in materials with a behavior depending on the oxidation state and in molecular switching capabilities due to hybridization change. , While various examples of PAHs presenting a single charged atom in their structure have been reported in different contributions, ,,,, doubly charged ones are less explored, with notable examples presenting O, N, S, or combinations of these heteroatoms, using both surface and solution-based chemistry. From this point of view, parent and π-extended dihydrophenazines represent valuable precursors toward the generation of 2 + N-doped PAHs. These derivatives are known to be easily oxidized and have been synthesized by various groups, leading to their use as emitters, redox-active materials, or organocatalysts. Interestingly, while the radical cations of such derivatives have been extensively explored, ,,, the aromatic dicationic diamagnetic states have been widely neglected and studied almost exclusively in solution, , with some notable exceptions successfully isolating N-alkyl derivatives of the parent phenazinium dication, which, however, were reported as highly reactive (Figure ). , More recently, an elegant work from the group of Shinokubo reported the synthesis of an anthracene-extended dihydrophenazine (Figure ), which was oxidized in solution to the radical and dicationic states, resulting in a marked electrochromism .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical inspections greatly concentrate on the HOMO and LUMO frontier orbitals. 38–41 The S 0 –S 1 transition in popular class I singlet fission chromophores is reasonably described by a HOMO–LUMO electronic transition. 42 Thus, the model Hamiltonian is constructed on local spin states of a pair of interacting H 2 -like molecules ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This result was similar to the oxidative dimerization of mono N-alkylated 5,12-dihydro-5,12-diazatetracene. 28 In 1969, VanAllan reported that the oxidation of BPO with various oxidants (cupric acetate, hydrogen peroxide, benzoquinone, cobalt acetate, and potassium permanganate) gave a dimer of BPO, and they assigned it to 3, but the structure of the dimer was not determined experimentally at that time. 29 Because we could not obtain good single crystals of 3 due to the low solubility, we synthesized the N-propylated derivative (3Pr) and succeeded in determining the connectivity of the dimer by the X-ray single crystal analysis (Figure S5).…”
Section: Introductionmentioning
confidence: 99%